2019
DOI: 10.1126/science.aaw5122
|View full text |Cite
|
Sign up to set email alerts
|

Programmable CRISPR-responsive smart materials

Abstract: Stimuli-responsive materials activated by biological signals play an increasingly important role in biotechnology applications. We exploit the programmability of CRISPR-associated nucleases to actuate hydrogels containing DNA as a structural element or as an anchor for pendant groups. After activation by guide RNA–defined inputs, Cas12a cleaves DNA in the gels, thereby converting biological information into changes in material properties. We report four applications: (i) branched poly(ethylene glycol) hydrogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
267
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(271 citation statements)
references
References 56 publications
3
267
0
1
Order By: Relevance
“…At the same time, they mounted the microfluidic chip on the fluorometer for detection in situ and succeeded in detecting the advent of whole Ebola RNA only with a detection limit of ∼20 pfu/mL (5.45 × 10 7 copies/mL). English et al reported that Cas12a‐based hydrogels in the form of a paper fluidic device could enable diagnostic readouts 57 . As shown in Figure 8, the intermediary layer includes PA‐DNA gel precursors so that together with ssDNA cross‐linker, it is supposed to form a hydrogel in the paper channels, which is related to the extent of degradation of the ssDNA gel cross‐linker.…”
Section: Crispr/cas–based In Vitro Diagnosticsmentioning
confidence: 99%
“…At the same time, they mounted the microfluidic chip on the fluorometer for detection in situ and succeeded in detecting the advent of whole Ebola RNA only with a detection limit of ∼20 pfu/mL (5.45 × 10 7 copies/mL). English et al reported that Cas12a‐based hydrogels in the form of a paper fluidic device could enable diagnostic readouts 57 . As shown in Figure 8, the intermediary layer includes PA‐DNA gel precursors so that together with ssDNA cross‐linker, it is supposed to form a hydrogel in the paper channels, which is related to the extent of degradation of the ssDNA gel cross‐linker.…”
Section: Crispr/cas–based In Vitro Diagnosticsmentioning
confidence: 99%
“…Developing superior smart materials has been pivotal to resolve industrial, environmental, and societal challenges. [1][2][3][4] The concept of preparing "materials on demand" or tailoring material design has fueled this field for the last decade. 5 Metal organic frameworks (MOFs) have proved to be a main player in this field following the guidelines of reticular chemistry and the well-defined structures of their secondary building units (SBUs) or molecular building blocks (MBBs).…”
mentioning
confidence: 99%
“…A key advantage of this system is, however, the possibility to modulate its degradation either with proteases, attacking its polymer backbone, or DNase, targeting the crosslinkers, without harming the overall structural stability of the gel. Future developments of this approach could include hydrogels with smart and programmable degradation profile, as suggested using CRISPR as a tool to create cleavable matrices …”
Section: Strategies To Evolve From Shape To Functionmentioning
confidence: 99%